2021
DOI: 10.1021/acscatal.1c00339
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Synthesis of Ethanol or Methyl Acetate via Dimethyl Oxalate Hydrogenation on Confined Iron Catalysts

Abstract: Oxygenated chemicals are essential to modern industries. However, selective syntheses with controllable products are still challenging over a single heterogeneous catalyst. Herein, a confined iron catalyst is designed for balanced syntheses of ethanol and methyl acetate via dimethyl oxalate (DMO) hydrogenation. With the characteristic structure of a microsphere, the Fe@C catalyst promotes the enrichment of hydrogen to reach a tunable selectivity of ethanol (84.3%) and methyl acetate (77.9%). The highest select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…In C 1s spectrogram, a weak peak at 283.5 eV for CÀ Fe bond can be observed on these catalysts, indicating the existence of iron ChemCatChem carbides species on the catalyst surface. In Fe 2p regions, 707.6, 709.8 and 712.1 eV are assigned to Fe x C, Fe 2 + and Fe 3 + , respectively, [28] which proves the coexistence of different iron oxides and iron carbides on surface of the three catalysts. Sun et al [28] believe the Fe 2 O 3 has no obvious activity on DMO conversion, and Fe 3 O 4 promotes conversion of MG in low H 2 / DMO molar ratio.…”
Section: Chemcatchemmentioning
confidence: 82%
See 2 more Smart Citations
“…In C 1s spectrogram, a weak peak at 283.5 eV for CÀ Fe bond can be observed on these catalysts, indicating the existence of iron ChemCatChem carbides species on the catalyst surface. In Fe 2p regions, 707.6, 709.8 and 712.1 eV are assigned to Fe x C, Fe 2 + and Fe 3 + , respectively, [28] which proves the coexistence of different iron oxides and iron carbides on surface of the three catalysts. Sun et al [28] believe the Fe 2 O 3 has no obvious activity on DMO conversion, and Fe 3 O 4 promotes conversion of MG in low H 2 / DMO molar ratio.…”
Section: Chemcatchemmentioning
confidence: 82%
“…In Fe 2p regions, 707.6, 709.8 and 712.1 eV are assigned to Fe x C, Fe 2 + and Fe 3 + , respectively, [28] which proves the coexistence of different iron oxides and iron carbides on surface of the three catalysts. Sun et al [28] believe the Fe 2 O 3 has no obvious activity on DMO conversion, and Fe 3 O 4 promotes conversion of MG in low H 2 / DMO molar ratio. However, Fe 3 O 4 cannot further convert MG to ethanol according to Sun's work.…”
Section: Chemcatchemmentioning
confidence: 82%
See 1 more Smart Citation
“…Numerous studies have shown that morphology regulation can effectively construct electrocatalytic materials with large specific surface area microstructures, such as hollow nanotube structured materials with remarkable bifunctional oxygen electrocatalytic properties prepared by self-template synthesis method [18]. Among these different structures, hollow core-shell sphere structure can provide high specific surface area and load more active sites [19], for example, using carbon layer as a substrate to fix the nanoparticles (NPs) or sub nanostructures has been widely reported [20][21][22][23]. Such hollow structure is helpful to stabilize the active sites and accelerate the mass transfer process in the electrochemical process [13].…”
Section: Introductionmentioning
confidence: 99%
“…1,6 In recent years, silver and copper based catalysts have been extensively researched for the heterogenetic reaction of DMO hydrogenation. 7–9 The Ag-based catalysts have been confirmed with high MG selectivity and stability at a reaction temperature of 473 K; however, the production rate was low due to the low activity of Ag metal towards CO bonds. 10,11 Copper-based catalysts could gain a high yield of EG and ethanol at the reaction temperature of 473 K and 553 K, respectively.…”
mentioning
confidence: 99%